Revenge by Castration: Breaking the Narrative Thread of Rape in Maria-Antònia Oliver’s Fiction - Diana Aramburu (Studies in 20th & 21st Century Literature, 2017)
Inspired by the feminist demonstrations of the late 1970s in Barcelona, Maria-Antònia Oliver responded to the crime of rape by incorporating the slogan that appeared following these protests, contra violació, castració (against rape, castration) in “Fils trencats” (Broken Threads), written in 1984 and published in her 1989 collection Tríptics (‘Leaflets’), and in Estudi en lila (Study in Lilac,1985), the first installment of the Lònia Guiu detective fiction trilogy. Since they distrust the police and the legal system to punish their assailants, the rape victims in these two narratives take justice into their own hands, removing the male body part that was used to victimize them. In “Fils trencats,” however, we witness the transformation of the victim into avenger, which we will analyze here, a process given visibility only at the end of Estudi en lila. Doubling as both victims and criminals, Oliver provides the narrative space for these victims to tell their respective stories and allows for an alternate form of justice to triumph. Using feminist scholarship that has concentrated on the rape-revenge film, such as that by Jacinda Read and Sarah Projansky, as well as criticism on literary representations of female violence by Helena González Fernández, this article will emphasize how Oliver tackles this lack of female victim visibility, and ushers in a new era for fictional responses to rape.
Keywords: Maria-Antònia Oliver; Tríptics; “Broken Threads”; gender violence; sexual assault; rape-revenge; feminist protests; Estudi en lila.